Infectious diseases screening approach among refugees: results from a single-center study - Fiore , Vito; De Vito, Andrea; Martineková, Petrana; Princic, Elija; Geremia, Nicholas; Madeddu, Giordano; Babudieri, Sergio (The Journal of Infection in Developing Countries, 2021)
Introduction: Our aim was to evaluate a screening program, with active case-finding and treatment for active tuberculosis (TB), latent tuberculosis infection (LTBI), blood-borne viruses (BBV), and sexually transmitted diseases (STDs) among refugees living in facility centers. Methodology: We collected data on refugees arriving to our attention in migrant centers in Sardinia, Italy. Socio-demographical data, anamnesis, and clinical features were collected. TST Mantoux was conducted, and X-ray chest (XRC) was performed if TST was positive. Blood-borne virus screening was proposed to all patients. Screening for STDs was offered according to guidelines, anamnesis, and physical examination. Results: Eighty-one patients were included. Seventy (86.4%) were male, and the mean age was 24.8±5.7 years. Thirty-three (40.7%) had scabies. Overall, 40/81 (49.4%) had a positive TST Mantoux. One (2.5%) was hospitalized and died for multi-drug-resistant TB. One (2.5%) patient had intestinal-TB. 52/81 (64.2%) refused HIV screening, whereas no positivity was found among tested migrants. Sixty-two (76.5%) accepted HCV screening, and one (1.6%) had a positive test. Fifty-eight (71.6%%) accepted HBV testing, and 29 (50%) of them had positive serology. Ten (12.3%) patients had anal or genital lesions due to syphilis, Molluscum contagiosum, and HPV in 7 (70%), 2 (20%), and one (10%) case, respectively. Conclusions: Infectious diseases control and prevention are a key strategy among refugees. The stay in a migrant center is an extraordinary occasion for healthcare provision. This condition could allow a broad screening program in which quick BBV screening tests could be a good method to implement uptake. More information and educational programs would allow a higher understanding and acceptance of HIV screening.